Scenario evolution modeling and probabilistic assessment of seawater intrusion accident in ports: An integrated framework combining disaster theory and multi-method simulation - Zhen Qiao; Xiaotiao Zhan (PLoS ONE, 2025)
As a typical marine disaster, seawater intrusion accidents have posed a serious threat to port production safety due to the double rise in the occurrence frequency and damage intensity. In favor of effectively controlling the scope of disaster impact and formulating more targeted emergency plans, it is particularly significant to carry out accident scenario evolution analysis. Based on the disaster system theory, this study constructed a model for the evolution of seawater intrusion accident scenarios in ports and clarified the probability of occurrence concerning each accident scenario by utilizing qualitative and quantitative methods. The main conclusions of this study were as follows: According to the theoretical framework of “disaster-causing body, disaster-affected body, and disaster-resistant body”, typical scenarios, such as concrete structure erosion and power supply interruption, were identified by scenario element method. By coupling the Petri net, cloud model, and Monte Carlo model, the quantitative derivation of evolutionary paths was realized, which not only retained the organic link between qualitative cognition and quantitative expression but also guaranteed the reliability of the results through ten thousand iterations. The probability grading system of accident scenarios was formed by combining the quantitative results. Among them, S11(Large equipment such as gantry and shore bridges stopped working due to power supply interruption) had the highest probability, with the corresponding value of 57.2%, and was in the “Moderately Likely” level according to the preset interval level. The research can provide a scientific basis for port enterprises to optimize the preparation with regard to emergency plans and improve the post-disaster recovery strategy, helping advance the comprehensive disaster prevention and mitigation capacity of ports.